Trifluralin and Corn Residues for Weed Management in Mung Bean Fields, Central Iraq - Mutar, Husam M.; Alsaadawi, Ibrahim S.; Lahmod, Nabil R. (Iraqi Journal of Science, 2022)
A field experiment was conducted  at two sites (Baghdad and Wasit Governorates) to evaluate the effects of allelopathic corn residues applied as soil incorporation or mulch, alone  and in combination  with reduced (50% of recommended dose) rate of trifluralin herbicide on weeds growth and mung bean yield. Conventional soil tillage and zero soil tillage treatments with corn residues were performed, while 50% dose and full dose of trifluralin only (without residues) treatments were included for comparison. Soil incorporation and mulch of corn residues reduced weed density and dry weight biomass and improved yield and yield components of mung bean in both sites. Mulch application was more effective than soil incorporation for weed control. However, the reduction in weed growth and the increase in mung bean yield were below the levels achieved by the label dose of herbicide. Application of 50% dose of trifluralin in plots incorporated or mulched with corn residues reduced weeds and scored yield similar to that achieved by 100% herbicide dose applied in both conventional and zero tillage plots. Chemical analysis revealed the presence of higher phenolics in plots amended with incorporated and mulched corn residues compared to their control plots. Chemical analysis also revealed that the periods of maximum quantities of phenolics paralleled with the periods of maximum suppressive activity against weed tested under field condition, which explains the phytotoxicity of phenolics on weed suppression. Such approach may help in reducing reliance upon high concentrations of trifluralin herbicide, improving the sustainability of agroecosystem, improving environmental safety, mitigating human health risks, and reducing the ability to tolerate herbicides.